Analysis of Mathematical critical thinking skills of Xl Students - Nufa visca amaratya; Rahma Dita Indriani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to analyze the critical thinking skills in mathematics of class X students. The research method used is survey research using tests of critical thinking skills in mathematics. Data was collected from class X students through a test specifically designed to measure their critical thinking skills in a mathematical context. Analysis was carried out to evaluate the level of students' critical thinking skills and the factors that influence them. The results showed that there was variation in students' critical thinking skills, with several factors such as educational background and level of motivation playing a role in influencing these skills.